Dielectric behavior of budding yeast in cell separation - Asami, Koji; Gheorghiu, Eugen; Yonezawa, Takeshi (Biochimica et biophysica acta, 1998)
Dielectric behavior of budding yeast in cell separation was studied by comparing two types of temperature-sensitive cell division cycle mutants that arrest before and after cell separation at the restrictive temperature. Single spherical cells before budding but after cell separation showed one main dielectric dispersion (centered at about 1 MHz) and one additional dielectric dispersion (at about 20 MHz), which were the Maxwell–Wagner dispersions due to the plasma membrane and due to both of the cell wall and vacuole, respectively. With cells that accumulated as doublets at a point immediately before cell separation, one more dielectric dispersion appeared around 200 kHz in addition to two dielectric dispersions similar to those found for the single cells without bud. The difference in dielectric behavior between the two types of cells might be mainly attributed to the difference in cell shape, which was theoretically examined using non-spherical cell models.